Perception of pharmacy students toward numeracy: An observational study from King Saud University, Riyadh Saudi Arabia - Ziyad Alrabiah; Azher Arafah; Muneeb U. Rehman; Wajid Syed; Salmeen Babelghaith; Abdulrahman Alwhaibi; Sultan Alghadeer; Abdulaziz Alhossan; Mohamed N. Al Arifi (Frontiers in Public Health, 2022)
Background and objectiveNumeracy is the branch of mathematics involved in understanding basic calculations, quantitation, estimation, reasoning, and execution of multistep operations. It is very imperative that pharmacists understand and apply numeracy skills in their routine work in the interest of their profession and patient care. This observational study was designed to assess the pharmacy student's perceptions of numeracy.MethodsA prospective observational study was conducted by the Department of Pharmacy, King Saud University, Kingdom of Saudi Arabia, between December 2021 and February 2022. All the enrolled subjects pursued a 5-year Pharma degree course at the university using a 9-item instrument, which accessed the perception of students toward numeracy. The data were analyzed using the statistical software statistical package for social science (SPSS) version 26.0 (SPSS Inc., Chicago, IL, USA). Chi-square and Fisher's exact test were used to derive an association between various parameters of the study subjects. A P-value of < 0.05 was taken as statistically significant.ResultsA total of 550 pharmacy students were approached in this study, out of which 21 (3.8%) students were excluded due to incompleteness of the responses; thereupon, 529 students were included in the study. We learned that almost 90.0% of students had excellent and/or good mathematical ability, but at the same time, they were frequent users of calculators. Most of the students endorsed the importance of numeracy and showed their interest in attaining more knowledge of numeracy. Similarly rating the perceptions of mathematical ability is significantly associated with the frequency of use of a calculator for calculations (p = 0.0001).ConclusionPharmacy students showed interest in numeracy and correspondingly showed excellent perceptions toward mathematical ability. Although the role of numeracy has been well accepted, inciting changes in teaching-learning practices through mathematically focused teaching approaches throughout the pharmacy program will increase its applicability in healthcare.